Corporate management in regional economy - G H Azashikov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2010)
The studies of the new methods of local self-government development facilitating local community resources' application toward the solution of the problems facing the society are gaining in importance against the backdrop of the crisis. The article provides the rationale for the potential application of corporate management principles to achieve the purpose involved.